Remedies available to Malaysian Islamic banks upon default of monthly payment by the customer in Musharakah Mutanaqisah (diminishing partnership) house financing - Othman, Ahmad Azam; Hassan, Rusni; Omar, Muhammad Naim; Mokhtar, Norlizah (2014)
Musharakah mutanaqisah (diminishing partnership) house financing (MMHF) is one type of house financing facilities that Islamic bank in Malaysia offers. It is a hybrid house financing product involving three recognized Shariah contracts that are musharakah (partnership), ijarah (leasing) and bay‘ (sale). Its modus operandi starts with the bank and the customer jointly purchase a particular house with an agreed ratio of contribution such as 90:10. The customer then leases the bank’s portion and at the same time purchases the bank’s portion progressively through monthly payment that consists of the monthly rental payment and purchase price. This results the bank’s ownership becomes diminished and the whole ownership of the house belongs to the customer at the end of the financing period. The issue is what happens when the customer defaults his monthly payment to the bank. Thus, this paper aims to investigate the remedies available to the bank upon default of the monthly payment by the customer. This is done by analyzing the MMHF agreement entered into between the bank and the customer. The findings from the analysis show that there are various available remedies to the bank due to default of monthly payment by the customer. The remedies include outstanding arrears payment, remaining acquisition payment, purchase of bank’s shares, purchase of customer’s shares and collateral right enforcement through sale.